Epidemiological Surveillance of Parvoviruses in Commercial Chicken and Turkey Farms in Guangxi, Southern China, During 2014–2019 - Zhang, Yanfang; Feng, Bin; Xie, Zhixun; Deng, Xianwen; Zhang, Minxiu; Xie, Zhiqin; Xie, Liji; Fan, Qing; Luo, Sisi; Zeng, Tingting; Huang, Jiaoling; Wang, Sheng (Frontiers in Veterinary Science, 2020)
A previously unidentified chicken parvovirus (ChPV) and turkey parvovirus (TuPV) strain, associated with runting-stunting syndrome (RSS) and poultry enteritis and mortality syndrome (PEMS) in turkeys, is now prevalent among chickens in China. In this study, a large-scale surveillance of parvoviruses in chickens and turkeys using conserved PCR assays was performed. We assessed the prevalence of ChPV/TuPV in commercial chicken and turkey farms in China between 2014 and 2019. Parvoviruses were prevalent in 51.73% (1795/3470) of commercial chicken and turkey farms in Guangxi, China. The highest frequency of ChPV positive samples tested by PCR occurred in chickens that were broiler chickens 64.18% (1041/1622) compared with breeder chickens 38.75% (572/1476) and layer hens 38.89% (112/288), and TuPV was detected in 70/84(83.33%). Native and exotic chicken species were both prevalent in commercial farms in southern China, and exotic broiler chickens had a higher positive rate with 88.10%(148/168), while native chickens were 50.00%(1465/2930). The environmental samples from poultry houses tested positive for ChPV and TuPV were 47.05% (415/874). Samples from open house flocks had higher prevalence rates of ChPV than those of closed house flocks (Table 5), among which those from the open house showed 84.16% (85/101) positivity, those from litter showed 62.86% (44/70) positivity, and those from drinking water showed 50.00% (56/112) positivity, whereas those from the closed house litter were 53.57% (60/112), those from swabs were 50.18% (138/275), and those from drinking water were 15.69% (32/204). Samples collected during spring were more frequently ChPV/ TuPV positive than those collected during other seasons.This study is the first report regarding the epidemiological surveillance of ChPV and TuPV in chicken/turkey flocks in Guangxi, China. Our results suggest that ChPV and TuPV are widely distributed in commercial fowl in Guangxi. These findings highlight the need for further epidemiological and genetic research on ChPV and TuPV in this area.